Design of extended surfactant-only EOR formulations for an ultrahigh salinity oil field by using hydrophilic lipophilic deviation (HLD) approach: From laboratory screening to simulation. (15th October 2019) - Wang, Shuoshi; Chen, Changlong; Yuan, Na; Ma, Yixin; Ogbonnaya, Onyekachi I.; Shiau, Benjamin; Harwell, Jeffrey H.
Highlights: The framework of HLD based chemical EOR formulation design is proposed. The number of the trial and error experiments are minimized. Proposed binary surfactant mixture could achieve ultra-low IFT (0.004 mN/m). No water treatment is required for the proposed system to reach 66% tertiary recovery. Surfactant scan is converted to salinity scan by HLD theory for simulation. Abstract: To address harsh brine issues of mature fields, extended surfactants with outstanding hardness tolerance were selected in this research. The involved surfactant and site crude oil were characterized against the hydrophilic-lipophilic deviation (HLD) theory (i.e., K, Cc and EACN values of the system). A surfactant-only formulation was successfully developed with a predictive tool of the HLD theory based on the microemulsion phase behaviors. The developed surfactant slug can be easily prepared in harsh formation brine of 161, 860 mg/L total dissolved solids (TDS) without any water pre-treatment with fast coalescence rate (<30 min) and excellent phase stability. The static IFT between the optimal surfactant brine mixture and site crude oil is 0.004 mN/m at reservoir temperature of 115 °F. The optimal surfactant formulations were further explored in one-dimensional sand pack tests under a representative condition. For further optimization, varying pore volumes of the chosen surfactant slugs were injected after water flooding and sand pack results showed tertiary oil recovery ranging from 52% to 66% of the residual oil (Sor). In addition, to better capture the transport properties of the developed surfactant formulations, the performances of sand packs were theoretically simulated with good match using the software package of UTCHEM in conjunction with the HLD theory. These results show that the correct determined HLD parameters predict the phase behavior in a good accuracy range under ultra-high salinity conditions with extended surfactants. Additionally, the phase behavior tests designed for targeted reservoir salinity could be readily used in salinity scan based simulation packages.